Model Development Of A Conwip System For Production Control In Multi-Stage Multiproduct Manufacturing Environments Consisting Of High-Runner And Low-Runner Product Families - Prakash, Joshua Jaya (2013)
Production control systems can be generally categorized as push or pull systems. In a push system, production is initiated at scheduled times, whereas in a pull system, production is initiated when a signal is received. However, there are limitations to each system. Push systems are controlled by observing throughput, which requires an estimation of system capacity. Inaccurate estimates can cause work-in-process (WIP) to increase beyond the limit. Pull systems require maintaining a small amount of WIP for each product family. Nevertheless, a large product mix may still result in a high WIP level. The aim of this research is to develop and investigate a new pull system (made up of several variants) known as a parallel constant work-in-process (CONWIP) system. In the systems, product families are classified into two classes (high-runner and low-runner) based on the demand of the product mix. Each class uses a CONWIP system, where production is initiated upon withdrawal of finished goods.